Six-Week Combined Vibration and Wobble Board Training on Balance and Stability in Footballers With Functional Ankle Instability - Cloak, R.; Nevill, A.; Day, S.; Wyon, M. (Clinical Journal of Sport Medicine, 2013)
Objective: To compare the effectiveness of a combination of vibration and wobble board training against wobble board training alone in footballers suffering from functional ankle instability (FAI).